Combining Valosin-containing Protein (VCP) Inhibition and Suberanilohydroxamic Acid (SAHA) Treatment Additively Enhances the Folding, Trafficking, and Function of Epilepsy-associated γ-Aminobutyric Acid, Type A (GABAA) Receptors - Han, Dong-Yun; Di, Xiao-Jing; Fu, Yan-Lin; Mu, Ting-Wei (The Journal of biological chemistry, 2015)
GABAA receptors are the primary inhibitory ion channels in the mammalian central nervous system. The A322D mutation in the α1 subunit results in its excessive endoplasmic reticulum-associated degradation at the expense of plasma membrane trafficking, leading to autosomal dominant juvenile myoclonic epilepsy. Presumably, valosin-containing protein (VCP)/p97 extracts misfolded subunits from the endoplasmic reticulum membrane to the cytosolic proteasome for degradation. Here we showed that inhibiting VCP using Eeyarestatin I reduces the endoplasmic reticulum-associated degradation of the α1(A322D) subunit without an apparent effect on its dynamin-1 dependent endocytosis and that this treatment enhances its trafficking. Furthermore, coapplication of Eeyarestatin I and suberanilohydroxamic acid, a known small molecule that promotes chaperone-assisted folding, yields an additive restoration of surface expression of α1(A322D) subunits in HEK293 cells and neuronal SH-SY5Y cells. Consequently, this combination significantly increases GABA-induced chloride currents in whole-cell patch clamping experiments than either chemical compound alone in HEK293 cells. Our findings suggest that VCP inhibition without stress induction, together with folding enhancement, represents a new strategy to restore proteostasis of misfolding-prone GABAA receptors and, therefore, a potential remedy for idiopathic epilepsy.The α1 subunit harboring the A322D mutation is subject to excessive ERAD. VCP inhibition using Eeyarestatin I reduces the ERAD of α1(A322D) subunits, and coapplication of SAHA additively enhances their proteostasis. Combining ERAD inhibition and folding enhancement yields significant functional rescue. This combination represents a new, promising strategy to treat epilepsy resulting from GABAA receptor misfolding.